Postictal punctate hippocampal diffusion restriction: the chicken or the egg? - Heckelmann, Jan; Weber, Yvonne; Dafotakis, Manuel; Wolking, Stefan (Frontiers in Neurology, 2025)
IntroductionMagnet resonance imaging (MRI) is the imaging gold standard for the evaluation of suspected epileptic seizures but also indispensable for detecting cerebral ischemia, using diffusion-weighted imaging (DWI) sequences. DWI restrictions can also occur following an epileptic seizure, thus mimicking cerebral ischemia. Postictal DWI lesions typically cross vascular territories and are confined to the cortex. Here, we present four illustrative cases with the unusual finding of reversible punctate postictal hippocampal DWI lesions, reminiscent of transient global amnesia (TGA).MethodsCase 1 was identified during video-EEG examination. We consecutively screened our database for similar cases, identifying three additional cases (3 male/1 female, age range 53–78 years). The initial MRI was performed within 5 days, a follow-up MRI within 4.5 months. All patients received video-EEG-monitoring.ResultsAll cases were initially referred for a first epileptic seizure. The occurrence of punctate hippocampal DWI lesions prompted the diagnosis of ischemic stroke with acute-symptomatic seizures. None of the patients featured classical symptoms of stroke or TGA. Follow-up MRIs were normal, ruling out ischemic stroke. During subsequent video-EEG workup one patient was diagnosed with epilepsy, the other patients with a first unprovoked seizure.ConclusionWe postulate that punctate hippocampal DWI lesions can be postictal phenomenon. Recognizing this imaging finding is relevant for the therapeutic management, we encourage referring patients for video-EEG monitoring in case of unconclusive findings. Besides vasogenic oedema related to neuronal hyperactivity, venous compression could be a potential pathomechanism. Prospective postictal imaging studies could help to better understand and quantify punctate hippocampal DWI lesions.